2018
DOI: 10.1002/prep.201800106
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of New Azide‐Nitrato‐Hydroxyl‐Terminated Polybutadiene by NaN3 and (NH4)2Ce(NO3)6

Abstract: This article reports way to functionalize hydroxyl‐terminated polybutadiene (HTPB) backbone by sodium azide and ceric ammonium nitrate, resulting in the formation of novel azide‐nitrato‐HTPB. In order to optimization of the effective parameters on the synthesis of azide‐nitrato‐HTPB, the starting material concentration, reaction time and temperature were investigated and the effect of these parameters on the azido‐nitrato functionalization of double bonds on HTPB backbone was evaluated. The functionalized HTPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Modified HTPB at 20:1 mass ratio presented the higher temperature T onset , attaining around 180°C. A series of works developed by Pant et al, 13 Ghayeni et al, 33,36 Cho et al 37 and Cegla et al 38 reported the lowering of the initial decomposition temperature of hydroxyl‐terminated polybutadiene when molecules are grafted in its chains, in agreement to what is found herein. The insert in Figure 5 shows that the modified HTPB samples have the same course of mass loss as the pristine HTPBs up to about 130°C.…”
Section: Resultssupporting
confidence: 87%
“…Modified HTPB at 20:1 mass ratio presented the higher temperature T onset , attaining around 180°C. A series of works developed by Pant et al, 13 Ghayeni et al, 33,36 Cho et al 37 and Cegla et al 38 reported the lowering of the initial decomposition temperature of hydroxyl‐terminated polybutadiene when molecules are grafted in its chains, in agreement to what is found herein. The insert in Figure 5 shows that the modified HTPB samples have the same course of mass loss as the pristine HTPBs up to about 130°C.…”
Section: Resultssupporting
confidence: 87%